Complex lower genitourinary reconstruction following combat-related injury. (1st March 2013) - Uppal, L; Anderson, P; Evriviades, Demetrius
Abstract : There is little data in the literature on the reconstruction of combat related lower genitourinary trauma. Published reports document patterns of injury, which is useful for epidemiological analysis of military trauma, but very few describe the reconstructive management. We aim to describe a systematic multidisciplinary approach to planning the challenging reconstruction of the severely injured male perineum.